Penegakan Hukum terhadap Tindak Pidana Phishing Dihubungkan dengan Undang Undang No 19 Tahun 2016 tentang Informasi dan Trasnsaksi Elektronik - Muhammad Akhdan Alif Rizaldy; Muhammad Gary Gagarin; muhamad Abas (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal regulation and the effectiveness of law enforcement against phishing crimes in Indonesia based on Law Number 19 of 2016 concerning Electronic Information and Transactions and Law Number 27 of 2022 concerning Personal Data Protection. This research employs an empirical juridical method using statutory and interview approaches. The findings indicate that the legal regulation of phishing remains general and has not fully accommodated the development of phishing methods. Law enforcement is also not yet optimal due to limited institutional capacity, low levels of digital literacy and the lack of victim reporting. Therefore, strengthening legal regulations and preventive measures is essential.